Evaluation of the significance of tumor stromal patterns and peri-tumoral inflammation in head and neck squamous cell carcinoma with special reference to the Yamamoto–Kohama classification - Geet Bhuyan; Prabir Hazarika; Anju M. Rabha (Indian Journal of Pathology and Microbiology)
Introduction: Head and neck squamous cell carcinoma (HNSCC) is the sixth most common cancer worldwide with 878,348 new cases. Cancer-associated fibroblasts (CAFs) are the predominant cell type in tumor stroma and are important promoters of tumor progression. Objective: The aim of the study was to evaluate the pattern of desmoplastic stromal reaction and peri-tumoral inflammatory infiltrate with the histological grade and clinical data. Materials and Methods: A total of 60 cases of HNSCC were included in the study. The hematoxylin and eosin (H and E)-stained sections from all cases were examined by two experienced pathologists for the grade, nature of stomal reaction (SR), peri-tumoral inflammatory infiltration, Yamamoto–Kohama classification grade, worst pattern of invasion (WPOI), depth of invasion (DOI), and other histopathological parameters. Correlation analysis was conducted using the Chi-square test. P-value less than 0.05 was considered statistically significant. Results: Immature SR was not observed in any of the well-differentiated squamous cell carcinoma (SCC) cases. However, one (3.7%) case of moderately differentiated SCC and two (28.6%) cases of poorly differentiated SCC showed signs of immature SR. In the case of the higher grades of the YK classification, specifically grades 4C and 4D, a more profound depth of tumor cell invasion, equal to or exceeding 10 mm, was evident in six (66.67%) and two (28.57%) cases, respectively. Additionally, among the seven (11.7%) cases classified as poorly differentiated carcinoma, three (42.85%) displayed a WPOI score of 5. Conclusion: SR and the tumor invasive pattern in HNSCC are related to prognosis and may indicate tumor aggressiveness.